Treatment of Eyebrow Hypotrichosis Using Bimatoprost: A Randomized, Double‐Blind, Vehicle‐Controlled Pilot Study. Issue 7 (25th April 2013) - Beer, Kenneth R.; Julius, Hillary; Dunn, Monica; Wilson, Fred
<x xml:space="preserve">Abstract</x> Background The Food and Drug Administration has approved bimatoprost ophthalmic solution (0.03%) for the treatment of eyelash hypotrichosis. Previous reports of its efficacy in eyebrow hypotrichosis are anecdotal. Objective To assess the efficacy and safety of bimatoprost 0.03% ophthalmic solution applied to the eyebrows in a randomized, double‐blind, vehicle‐controlled study. Methods Subjects (n = 20) with mild to moderate eyebrow hypotrichosis enrolled in the study. One group (Bim) applied bimatoprost to each eyebrow daily for 9 months, and another applied vehicle nightly to each eyebrow for 5 months. Subjects in the latter group were re‐randomized to apply bimatoprost (Veh‐Bim Group) or vehicle (Veh Group) daily to each eyebrow for 4 months. The primary end point was investigator‐assessed eyebrow appearance; secondary end points were subject‐reported outcomes. Results Investigator assessments showed significant improvements from baseline to 6 (p = .002) and 7 (p = .005) months for the eyebrows treated with bimatoprost. p‐Values for the Veh‐Bim and Veh groups were not significant at any time point. End‐of‐study subject satisfaction with eyebrow fullness or thickness and darkness or color was greater in the Bim group than in the Veh group. Adverse effects were not observed. Conclusion Bimatoprost 0.03% ophthalmic solution applied daily for 9 months improves the appearance of eyebrows noticeably more than vehicle, without side effects.